KAPASITAS PEMERINTAH DAERAH DALAM PENANGGULANGAN BENCANA ALAM TANAH LONGSOR DI KABUPATEN SUMEDANG PROVINSI JAWA BARAT - Hj Ai Nunung (POLITEKNIK PIKSI GANESHA, 2020)
Landslide natural disaster program that occurred in several areas, especially in Sumedang Regency, this research was made to find out how the local government is responsible for handling landslide natural disasters in Sumedang Regency, West Java Province. The main objective of this study is to determine the capacity of the local government in overcoming landslide natural disasters. which is a very important measurement tool for determining the success of disaster risk reduction in the Sumedang region. This very complex task must be supported by human resources who have high competence in planning, implementing plans, organizing, leadership, supervising or controlling development and so on. Assessment of the capacity of regional governments in managing landslides is one of the parameters in determining the success in anticipating the impact of landslide hydrometeorological disasters. The reference for the capacity assessment in Indonesia is based on Ina RISK's analysis of disaster sites, which are undulating hills at an altitude between 700 and 750 meters above sea level. The slope is steep, and below it is a residential area. The factors that cause ground motion are estimated to be due to the slope of the slope which is rather steep to steep. Not only that, the weathering of the breccias and tuffs that easily release water underneath is a waterproof layer so that it functions as a sliding area. Cliffs that experience landslides are open land without strong rooted vegetation and without slope reinforcement, besides that drainage channels according to the Geological Agency of the Ministry of Energy and Mineral Resources, land movement disasters or landslides in Cimanggung District, Sumedang Regency, West Java Province the upper slopes of the settlement. Landslide disaster management in the area has to be evacuated and must anticipate the potential for further landslides considering that the area is still prone to landslides and high rainfall. According to PVMBG, the capacity of landslides in Sumedang Regency is Grade B, namely 70% -80% of the 88 indications studied. From these results, the main concern of the Landslide Disaster Management Agency was triggered by high rainfall and unstable soil conditions. BNPN increases the provincial BPPD to carry out early warning and preparedness, especially BPPD Sumedang Regency Key words: Capacity, landslide disaster